The Influence of Islam in Local Historiography in Jambi in the XVIII Century - Bella Wahyuni; Dennys Pradita (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2022)
Islam entered Nusantara several centuries ago. The arrival of Islam in Nusantara influenced religiosity, thought, and a system of government that adopted Islamic values. One of the areas in Nusantara that Islamization influenced was Jambi sultanate. The influence of the Islamization process can be seen in several writings or literary works in the form of laws, literary works, or other writings. Therefore, this research looks at these two values from a historical point of view and Islamic values. The historical point of view is seen from the point of view of writing, the soul of the era, and the records recorded in the text. In contrast, Islamic values are seen from several elements, such as the Arabic script and other factors absorbed in writing. This paper uses the historical method with a philological approach. This study's results indicate that several local works in the Jambi area have undergone changes in content or several other elements. This can be seen in Tanjung Tanah text and Jambi Charter's text. In both manuscripts, Islamic influences can be seen in Arabic letters, greetings, some ornaments, and the text's contents. Some of these elements replaced the dominant role of the Hindu-Buddhist features that had developed in the previous decades in Jambi. Still, some local elements or Hindu-Buddhist influences were not immediately removed from the text.